2020
DOI: 10.1039/d0sm00173b
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained Monte Carlo simulations of nanogel–polyelectrolyte complexes: electrostatic effects

Abstract: Coarse-grained model of nanogel–polyelectrolyte complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…As can be seen, there are three pairs of hydrogels with the same polymer volume fractions (0.06, 0.09, and 0.13, gels 7 and 11, 8 and 12, and 5 and 9, respectively) but different values of N mu and mesh size. Other parameters used in these simulations were k e = 0.4 N/m, R s = 0.633 nm, T = 298 K, η = 0.000891 Pa·s, and ε WCA = 4.11 × 10 –21 J (the value of this parameter was used in previous works ). None of them was adjustable.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, there are three pairs of hydrogels with the same polymer volume fractions (0.06, 0.09, and 0.13, gels 7 and 11, 8 and 12, and 5 and 9, respectively) but different values of N mu and mesh size. Other parameters used in these simulations were k e = 0.4 N/m, R s = 0.633 nm, T = 298 K, η = 0.000891 Pa·s, and ε WCA = 4.11 × 10 –21 J (the value of this parameter was used in previous works ). None of them was adjustable.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Sennato et al have shown that when PNIPAM microgels are collapsed, they strongly interact with oppositely charged polyelectrolytes and a large charge inversion is observed [ 56 ]. In this sense, coarse-grained Monte Carlo simulations have recently been applied to predict the charge inversion previously detected through µ e for nanogel-polyelectrolyte complexes [ 57 ]. Therein, it is demonstrated that charge inversion occurs only if the polyelectrolyte charge is large enough [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, coarse-grained Monte Carlo simulations have recently been applied to predict the charge inversion previously detected through µ e for nanogel-polyelectrolyte complexes [ 57 ]. Therein, it is demonstrated that charge inversion occurs only if the polyelectrolyte charge is large enough [ 57 ]. Apart from the reversal observed in the sign of the µ e shown in Figure 3 , we can also observe that the isoelectric point of DNA/mGel+ complexes does not depend on the temperature, i.e., the swelling state of the mGel+.…”
Section: Resultsmentioning
confidence: 99%
“…In these simulations, elastic forces satisfy Hooke’s law: where is the force that particle exerts on particle , is the elastic constant, is the distance between particles and , is the bond length at equilibrium and is the unit vector pointing from particle to particle . As in previous works [ 43 ], N/m and nm (the diameter of monomeric units).…”
Section: Model and Simulationsmentioning
confidence: 99%